Town Creek Indian Mound : a Native American Legacy. - Coe, Joffre Lanning (University of North Carolina Press, 1995)
The temple mound and mortuary at Town Creek, in Montgomery County, is one of the few surviving earthen mounds built by prehistoric Native Americans in North Carolina. It has been recognized as an important archaeological site for almost sixty years and, as a state historic site, has become a popular destination for the public. This book is Joffre Coe's illustrated chronicle of the archaeological research conducted at Town Creek, a project with which Coe has been intimately involved for more than fifty years, since its inception as a WPA program in 1937.